Architectured heterogeneous alloys with selective laser melting. (1st February 2022) - Jeong, Sang Guk; Karthik, Gangaraju Manogna; Kim, Eun Seong; Zargaran, Alireza; Ahn, Soung Yeoul; Sagong, Man Jae; Kang, Suk Hoon; Cho, Jung-Wook; Kim, Hyoung Seop
Abstract: Hetero-structuring is considered as one of the effective strengthening routes in metallic materials to realize excellent strength-ductility synergy. However, tailoring several microstructural features in these heterogeneous materials is challenging. In this work, we demonstrate a new capability of selective laser melting in controlling the site-specific microstructures and developing architectured heterogeneous materials. The heterostructured stainless steel samples demonstrated an excellent combination of strength and ductility compared to homogeneous materials. The current approach is versatile and can be used for many printable alloys. Further, this work opens a new direction in metal additive manufacturing to produce heterostructured materials for enhanced strength and ductility. Graphical abstract: Image, graphical abstract